Hubungan Pengetahuan dan Sikap Orangtua tentang Penanganan Pertama Pada Anak yang Tersedak di Huta III Kabupaten Simalungun - Nabilah Siregar; Yohanna Adelina Pasaribu (Universitas Batanghari Jambi, 2022)
Choking is an emergency situation that often occurs in community, especially in children. If the choking incident is not treated immediately, it can lead to oxygen deficiency conditions which can result in death. This study aims to determine the relationship between knowledge and attitudes of parents about the first treatment of a choking child in Huta III, Simalungun Regency. This type of research is an observational analytic study with a cross sectional design, and data analysis used Chi Square test. The results showed that the majority of respondents (15 people or 40.5%) have less knowledge, 18 people (48.6%) respondents have negative attitudes, and there was a relationship between knowledge and parental attitudes about handling children who were choking (p value 0.001 ). Therefore, nurses as one of the health workers in the community have to give special attention through health education about the first treatment for children who are choking to increase the knowledge and attitudes of parents.